Anomalous behavior of the Hall effect in electron-doped superconductor Nd2-xCexCuO4+d with nonstoichiometric disorder - Charikova, T.B.; Shelushinina, N.G.; Harus, G.I.; Neverov, V.N.; Petukhov, D.S.; Sochinskaya, O.E.; Ivanov, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Magnetoresistivity and Hall effect measured in magnetic fields up to B = 9 T (B ║ c, J ║ ab) in electrondoped Nd2-xCexCuO4+d single crystal films with x = 0.14; 0.15; 0.18 and different oxygen content (δ) were studied in a temperature range of 0.4–4.2 K. The resistivity and Hall coefficient behaviors in the mixed state are discussed in the framework of flux-flow model with the inclusion of the back-flow of vortices owing to the pinning forces.